Measurement of the Environmental Impact of Materials - Simon, Franz-Georg; Kalbe, Ute (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Throughout their life cycles-from production, usage, through to disposal-materials and products interact with the environment (water, soil, and air). At the same time, they are exposed to environmental influences and, through their emissions, have an impact on the environment, people, and health. Accelerated experimental testing processes can be used to predict the long-term environmental consequences of innovative products before these actually enter the environment. We are living in a material world. Building materials, geosynthetics, wooden toys, soil, nanomaterials, composites, wastes and more are research subjects examined by the authors of this book. The interactions of materials with the environment are manifold. Therefore, it is important to assess the environmental impact of these interactions. Some answers to how this task can be achieved are given in this Special Issue.